1989
DOI: 10.1007/bf01658870
|View full text |Cite
|
Sign up to set email alerts
|

The use of the preperitoneal approach for the simultaneous repair of inguinal hernia during surgery on the bladder and prostate

Abstract: Repair of a hernia can be performed safely and expeditiously during a radical pelvic operation by the preperitoneal approach through a median longitudinal incision. We present the results of 41 preperitoneal herniorrhaphies performed simultaneously with 343 radical retropubic prostatectomies and 26 radical cystoprostatectomies. There was no evidence of hernial recurrence after a mean of 28 months and no complications attributable to the hernial repairs. We illustrate the preperitoneal anatomy, and the techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…However, our data supported by others [2,8,9] clearly demonstrate that this complication is relatively uncommon. In fact, patients undergoing radical retropubic prostatectomy are not likely to have a urinary tract infection while in patients undergoing Rinjack operation the urine can be sterilized before the procedure with a suitable antibiotic prophylaxis if silent urinary infection is suspected or apparent.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, our data supported by others [2,8,9] clearly demonstrate that this complication is relatively uncommon. In fact, patients undergoing radical retropubic prostatectomy are not likely to have a urinary tract infection while in patients undergoing Rinjack operation the urine can be sterilized before the procedure with a suitable antibiotic prophylaxis if silent urinary infection is suspected or apparent.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, given the high frequency of 'prostatic open surgery', simultaneous repair of preexisting hernias seems to be a practical and logical choice since it avoids added morbidity associated with hernias, reducing too the risk of damage to the testicular vessels and sensory nerves. Several surgeons perform the modifi ed technique of Nyhus et al However, if it is true that a lax internal ring or a small indirect hernia can be repaired with a few sutures without tension in the surrounding tissues, the principal drawback of this method is an unavoidable tension on the repair for large defects and when the supporting tissues are atrophic [1][2][3][4]13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Open extraperitonal radical retropubic prostatectomy could be combined with inguinal hernia repair without additional complications. 16,17 Lee et al 18 reported repair of 48 hernias in 40 patients undergoing laparoscopic radical prostatectomy. They reported no increase in complications and no hernia recurrences.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is more diYcult to account for inguinal hernias after laparoscopic radical prostatectomy. Subclinical inguinal hernias are found in 5-33% of patients undergoing radical prostatectomy [9][10][11][12]. This suggests that rather than being caused by the surgery, inguinal hernias found post-RP may represent subclinical hernias that become manifest after surgery.…”
Section: Introductionmentioning
confidence: 92%